Nonaqueous electrolyte secondary battery
By attaching sulfonic acid compounds to the positive electrode active substance of the nonaqueous electrolyte secondary battery and setting appropriate compressive strength in the negative electrode core, the problem of reducing charge and discharge capacity caused by the reduction of the positive electrode elongation rate is solved, and a high-capacity nonaqueous electrolyte secondary battery is realized.
Patent Information
- Application Number
- CN202380060080.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-07-21
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to realize high-capacity nonaqueous electrolyte secondary batteries, especially when the elongation of the break of the positive electrode is reduced, resulting in a reduction in the charge and discharge capacity of the winding battery.
By attaching a sulfonic acid compound to the surface of the lithium-containing transition metal composite oxide particles of the positive electrode active material, and a 1% negative electrode mixture layer with a compressive strength of 300 MPa or less is provided in the negative electrode core, the winding property and charge and discharge capacity of the electrode body are improved.
The reduction of the positive electrode elongation rate is effectively suppressed, the winding properties of the electrode body are improved, and the charging and discharge capacity of the winding type nonaqueous electrolyte secondary battery is increased.
Smart Images

Figure CN119731835A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery. Background Art
[0002] Patent document 1 proposes that Li4Ti5O 12 An active material having a surface layer composed of a lithium sulfonate compound formed on the surface of lithium titanate particles as a main component. Patent Document 1 states that by using this active material in a negative electrode active material, a change in resistance of a battery before and after charge storage can be suppressed.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-6164 Summary of the invention
[0006] In non-aqueous electrolyte secondary batteries, achieving high capacity is an important issue. Conventional technologies including Patent Document 1 cannot fully address such issues, and there is still much room for improvement.
[0007] The non-aqueous electrolyte secondary battery disclosed herein is characterized in that it is a non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, the positive electrode comprising a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of particles of the composite oxide, the sulfonic acid compound being a compound represented by formula (I), the negative electrode comprising a negative electrode core and a negative electrode mixture layer formed on the surface of the negative electrode core, and the 1% compressive strength of the negative electrode core being less than 300 MPa.
[0008]
[0009] In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.
[0010] The nonaqueous electrolyte secondary battery disclosed herein can achieve a high capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment.
[0012] Figure 2 This is a diagram showing the relationship between strain and stress when a tensile test is performed on a negative electrode core. DETAILED DESCRIPTION
[0013] The research results of the present inventors have made it clear that by making the sulfonic acid compound shown in the above formula (I) present on the particle surface of the lithium-containing transition metal composite oxide used as the positive electrode active material, a high-capacity non-aqueous electrolyte secondary battery can be achieved. It is believed that the reason is that the reaction resistance in the positive electrode is reduced by the function of the sulfonic acid compound, and the charge and discharge depth can be deepened. However, in the case where the lithium-containing transition metal composite oxide containing such a sulfonic acid compound is used as the positive electrode active material, a new problem of a significant reduction in the elongation at break of the positive electrode is generated. In a wound non-aqueous electrolyte secondary battery having an electrode body formed by winding the positive electrode and the negative electrode with a separator, if the elongation at break of the positive electrode is reduced, the size of the winding core during winding will become larger. In the case where the battery size is fixed, if the size of the winding core becomes larger, the length of the electrode body becomes shorter, and as a result, the charge and discharge capacity of the wound non-aqueous electrolyte secondary battery is reduced.
[0014] As described above, when the sulfonic acid compound is applied to the surface of the particles of the lithium-containing transition metal composite oxide, it specifically functions to reduce the reaction resistance in the positive electrode and deepen the charge and discharge depth of the positive electrode, but when the sulfonic acid compound is applied only to the positive electrode, a high-capacity wound non-aqueous electrolyte secondary battery cannot be achieved. Specifically, compared with the effect of high capacity brought about by the use of a positive electrode active material containing a sulfonic acid compound in the positive electrode, the effect of the reduction in charge and discharge capacity due to the increase in the core size accompanied by the reduction in the elongation at break of the positive electrode becomes more significant, and the charge and discharge capacity of the wound non-aqueous electrolyte secondary battery as a whole is reduced.
[0015] Therefore, the inventors of the present invention conducted in-depth research to solve the above-mentioned problems, and the results confirmed that: when using a positive electrode active material containing a sulfonic acid compound, the 1% compressive strength of the negative electrode core has a specific effect on the size of the winding core during winding. Specifically, by setting the 1% compressive strength of the negative electrode core to less than 300 MPa, the winding property of the electrode plate during the production of the electrode body is improved, and the increase in the diameter of the winding core associated with the decrease in the elongation at break of the positive electrode can be suppressed. In other words, if the 1% compressive strength of the negative electrode core exceeds 300 MPa, the winding property of the electrode body is significantly reduced, and the diameter of the winding core will increase.
[0016] In addition, a lithium-containing transition metal composite oxide with a sulfonic acid compound attached to the particle surface is used as a positive electrode active material, and a negative electrode core having a 1% compressive strength of 300 MPa or less is used, thereby successfully increasing the charge and discharge capacity of a wound non-aqueous electrolyte secondary battery. According to the wound non-aqueous electrolyte secondary battery disclosed in the present invention, by using a negative electrode core having a 1% compressive strength of 300 MPa or less, the winding property of the electrode plate when making the electrode body is improved, and the increase in the size of the winding core accompanied by the reduction in the elongation at break of the positive electrode can be suppressed. As a result, the length of the electrode body can be lengthened, and the effect of high capacity brought about by the presence of the sulfonic acid compound in the positive electrode can be further exerted.
[0017] Hereinafter, an example of an embodiment of the nonaqueous electrolyte secondary battery of the present disclosure will be described in detail with reference to the drawings. It should be noted that a configuration obtained by selectively combining the various configuration features of the multiple embodiments and modifications described below is included in the scope of the present disclosure.
[0018] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 includes a wound electrode body 14, a nonaqueous electrolyte, and an outer can 16 for storing the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a winding structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with one end side open in the axial direction, and the opening of the outer can 16 is blocked by a sealing body 17. In the following, for convenience of description, the sealing body 17 side of the battery is set as the upper side, and the bottom side of the outer can 16 is set as the lower side.
[0019] The non-aqueous electrolyte has lithium ion conductivity and may be a liquid electrolyte (electrolyte) or a solid electrolyte.
[0020] Liquid electrolyte (electrolyte) comprises non-aqueous solvent and electrolyte salt dissolved in non-aqueous solvent. Non-aqueous solvent can use ester, ether, nitrile, amide and these two kinds of mixed solvent etc. for example. As an example of non-aqueous solvent, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and their mixed solvent etc. can be cited. Non-aqueous solvent can also contain halogen substitution (for example, fluoroethylene carbonate etc.) formed by at least a part of hydrogen of these solvents being replaced by halogen atoms such as fluorine. Electrolyte salt uses lithium salt such as LiPF6 for example.
[0021] As a solid electrolyte, for example, a solid or gel-like polymer electrolyte, an inorganic solid electrolyte, etc. can be used. As an inorganic solid electrolyte, a well-known material in a fully solid lithium-ion secondary battery, etc. (for example, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a halogen-based solid electrolyte, etc.) can be used. The polymer electrolyte, for example, comprises a lithium salt and a matrix polymer, or comprises a non-aqueous solvent, a lithium salt and a matrix polymer. As a matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent for gelation is used. As polymer materials, fluororesins, acrylic resins, polyether resins, etc. can be listed.
[0022] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are alternately stacked in the radial direction of the electrode body 14 by being wound into a spiral shape. The negative electrode 12 is formed to be one circle larger than the positive electrode 11 to prevent the precipitation of lithium. That is, the negative electrode 12 is formed longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one circle larger than the positive electrode 11, for example, two sheets are arranged in a manner of clamping the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0023] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1 In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23 serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.
[0024] A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed on the outer can 16, in which a part of the side portion protrudes inward and supports the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 through the groove portion 22 and the open end of the outer can 16 fastened to the sealing body 17.
[0025] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.
[0026] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 will be described in detail.
[0027] [positive electrode]
[0028] The positive electrode 11 has a positive electrode core 30 and a positive electrode mixture layer 31 disposed on the surface of the positive electrode core 30. The positive electrode core 30 can use a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film of the metal disposed on the surface, or the like. The positive electrode mixture layer 31 contains a positive electrode active material, a conductive agent, and a binder, and is preferably disposed on both sides of the positive electrode core 30 except for the portion connected to the positive electrode lead 20. The positive electrode 11 can be manufactured, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, and a binder to the surface of the positive electrode core 30, drying the coating, and then compressing to form the positive electrode mixture layer 31 on both sides of the positive electrode core 30.
[0029] As the conductive agent contained in the positive electrode mixture layer 31, carbon black such as acetylene black and Ketjen black, graphite, carbon nanotubes (CNT), carbon nanofibers, graphene and other carbon materials can be exemplified. As the binder contained in the positive electrode mixture layer 31, fluorine-containing resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. In addition, these resins can also be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide, etc. The content of the conductive agent and the binder is, for example, 0.1 to 5.0% by mass relative to the mass of the positive electrode mixture layer 31.
[0030] The positive electrode 11 includes a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of the composite oxide particles. The lithium-containing transition metal composite oxide with the sulfonic acid compound attached to the particle surface functions as a positive electrode active material. The sulfonic acid compound is a compound represented by formula (I).
[0031]
[0032] In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.
[0033] The sulfonic acid compound represented by formula (I) (hereinafter, sometimes referred to as "sulfonic acid compound") reduces the reaction resistance in the positive electrode 11 and improves the output characteristics of the battery. In addition, as the resistance is reduced, the charge and discharge depth can be deepened, and high capacity can be achieved. The sulfonic acid compound exerts this effect even in a very small amount, and preferably exists on the particle surface of the composite oxide in an amount of 0.01% by mass or more relative to the mass of the lithium-containing transition metal composite oxide. The content of the sulfonic acid compound is more preferably 0.05% by mass or more, and particularly preferably 0.10% by mass or more relative to the mass of the lithium-containing transition metal composite oxide.
[0034] The upper limit of the content of the sulfonic acid compound is not particularly limited, but from the viewpoint of improving the winding property of the electrode plate when manufacturing the electrode body, it is preferably 2.0% by mass, more preferably 1.5% by mass, and particularly preferably 1.0% by mass relative to the mass of the lithium-containing transition metal composite oxide. The sulfonic acid compound is present, for example, in an amount of 0.05 to 1.50% by mass or 0.1 to 1.0% by mass relative to the mass of the lithium-containing transition metal composite oxide.
[0035] The positive electrode active material may be mainly composed of composite particles of lithium-containing transition metal composite oxides with sulfonic acid compounds attached to the particle surface, and may be substantially composed of the composite particles. It should be noted that the positive electrode active material may also contain composite oxides or other compounds other than the composite particles within the scope of not impairing the purpose of the present disclosure.
[0036] The lithium-containing transition metal oxide preferably has a layered rock salt structure. As the layered rock salt structure of the lithium-containing transition metal oxide, for example, a layered rock salt structure belonging to the space group R-3m, a layered rock salt structure belonging to the space group C2 / m, etc. can be cited. Among them, from the viewpoint of high capacity and stability of the crystal structure, a layered rock salt structure belonging to the space group R-3m is preferred. The layered rock salt structure of the lithium-containing transition metal oxide comprises a transition metal layer, a Li layer and an oxygen layer.
[0037] The lithium-containing transition metal oxide is a composite oxide containing metal elements such as Co, Mn, Ni, and Al in addition to Li. The metal element constituting the lithium-containing transition metal oxide is, for example, at least one selected from Mg, Al, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Y, Zr, Sn, Sb, W, Pb, and Bi. Among them, it is preferred to contain at least one selected from Co, Ni, and Mn. As an example of a suitable composite oxide, a composite oxide containing Ni, Co, and Mn and a composite oxide containing Ni, Co, and Al can be listed.
[0038] From the viewpoint of high capacity, the lithium-containing transition metal oxide contains preferably 70 mol% or more, more preferably 80 mol% or more Ni relative to the total molar number of metal elements other than Li. In addition, the effect of adding the sulfonic acid compound is more significant when a lithium-containing transition metal oxide with a high Ni content is used. The Ni content can be 85 mol% or more, or 90 mol% or more relative to the total molar number of metal elements other than Li. The upper limit of the Ni content is, for example, 95 mol%.
[0039] As described above, an example of a suitable lithium-containing transition metal oxide is a composite oxide containing Ni, Co, and Al. Relative to the total molar number of metal elements other than Li, the content of Al is 4 to 15 mol%, and the content of Co is less than 1.5 mol%. If the content of Al is within this range, it helps to stabilize the crystal structure and improve the cycle characteristics. Co may not be substantially added, and the battery performance is improved by adding a small amount of Co.
[0040] Lithium-containing transition metal oxides are, for example, a Ni x Al y Co z M1 w O 2-b (wherein, 0.8≤a≤1.2, 0.85≤x≤0.95, 0.04≤y≤0.15, 0≤z≤0.015, 0≤w≤0.15, 0≤b<0.05, x+y+z+w=1, M1 is at least one element selected from the group consisting of Mn, Fe, Ti, Si, Nb, Zr, Mo and Zn.) A composite oxide represented by M1 is preferably Mn.
[0041] The content of elements constituting the lithium-containing transition metal composite oxide can be measured by using an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.
[0042] The lithium-containing transition metal composite oxide is, for example, a secondary particle formed by the aggregation of multiple primary particles. The volume-based median particle size (D50) of the composite oxide is not particularly limited, and as an example, it is 3 μm to 30 μm, preferably 5 μm to 25 μm. In the case where the composite oxide is a secondary particle formed by the aggregation of primary particles, the D50 of the composite oxide refers to the D50 of the secondary particle. D50 refers to the particle size at which the cumulative frequency from the smaller particle size in the volume-based particle size distribution becomes 50%, also known as the median diameter. The particle size distribution of the composite oxide (the same is true for the negative electrode active material) is measured using a laser diffraction particle size distribution measuring device (for example, Microtrac Bell Inc., MT3000II) and water as the dispersion medium.
[0043] The average particle size of the primary particles constituting the lithium-containing transition metal composite oxide is, for example, 0.05 μm to 1 μm. The average particle size of the primary particles is calculated by averaging the diameters of the circumscribed circles of the primary particles extracted by analyzing a scanning electron microscope (SEM) image of a cross section of the secondary particles.
[0044] As described above, the sulfonic acid compound present on the surface of the particles of the lithium-containing transition metal composite oxide is a compound represented by formula (I).
[0045]
[0046] In the formula, A is an element of Group 1 or Group 2, R is a hydrocarbon group, and n is 1 or 2. A is preferably an element of Group 1. Among them, Li or Na is more preferred, and Li is particularly preferred.
[0047] In formula (I), R is preferably an alkyl group. The carbon number of the alkyl group is preferably 5 or less, more preferably 3 or less. From the viewpoint of reducing the reaction resistance, an example of a suitable R is an alkyl group having a carbon number of 3 or less, wherein a methyl group is preferred. It should be noted that, in R, a portion of the hydrogen bonded to the carbon may also be substituted by fluorine. In addition, n in formula (I) is preferably 1.
[0048] Specific examples of the sulfonic acid compound include lithium methanesulfonate, lithium ethanesulfonate, lithium propanesulfonate, sodium methanesulfonate, sodium ethanesulfonate, magnesium methanesulfonate, lithium fluoromethanesulfonate, etc. Among them, at least one selected from the group consisting of lithium methanesulfonate, lithium ethanesulfonate and sodium methanesulfonate is preferred, and lithium methanesulfonate is particularly preferred.
[0049] The sulfonic acid compound is, for example, uniformly present on the entire surface of the particles of the lithium-containing transition metal composite oxide. The presence of the sulfonic acid compound on the surface of the particles of the lithium-containing transition metal composite oxide can be confirmed by Fourier transform infrared spectroscopy (FT-IR). In the infrared absorption spectrum obtained by FT-IR, the positive electrode active material containing lithium methanesulfonate, for example, has a peak at 1238 cm -1、1175cm -1 、1065cm -1 、785cm -1 There is an absorption peak near 1238cm -1 、1175cm -1 、1065cm -1 The peaks near 785cm are caused by the SO stretching vibration of lithium methanesulfonate. -1 The nearby peaks are peaks derived from CS stretching vibration of lithium methanesulfonate.
[0050] For positive electrode active materials containing sulfonic acid compounds other than lithium methanesulfonate, the presence can also be confirmed by the absorption peak derived from the sulfonic acid compound in the infrared absorption spectrum. It should be noted that the presence of the sulfonic acid compound on the surface of the particles of the lithium-containing transition metal composite oxide can also be confirmed by ICP, atomic absorption spectroscopy, X-ray photoelectron spectroscopy (XPS), radioactive light XRD measurement, TOF-SIMS, etc.
[0051] The positive electrode active material as an example of the embodiment can be produced by the following method. It should be noted that the production method described here is an example, and the production method of the positive electrode active material is not limited to this method.
[0052] First, a metal oxide containing metal elements such as Ni, Al, Co, and Mn is synthesized. Then, the metal oxide and a lithium compound are mixed and calcined to obtain a lithium-containing transition metal composite oxide. The metal oxide is synthesized, for example, by stirring a solution of a metal salt containing Ni, Al, Co, Mn, etc. while dropping an alkaline solution such as sodium hydroxide, adjusting the pH to the alkaline side (for example, 8.5 to 12.5), thereby precipitating (coprecipitating) a composite hydroxide containing metal elements such as Ni, Al, Co, and Mn, and heat-treating the composite hydroxide to enable synthesis. The heat treatment temperature is not particularly limited, and as an example, it is 300°C to 600°C.
[0053] Examples of lithium compounds include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. The metal oxide and the lithium compound are mixed, for example, in a molar ratio of the metal element in the metal oxide to Li in the lithium compound of 1:0.98 to 1:1.1. It should be noted that when mixing the metal oxide and the lithium compound, other metal raw materials may be added as needed.
[0054] The mixture of the metal oxide and the lithium compound is calcined, for example, in an oxygen atmosphere. The mixture can also be calcined through multiple temperature increase processes. The calcination process includes the following steps: a first temperature increase process of heating to 450°C to 680°C at a temperature increase rate of, for example, 1.0°C / min to 5.5°C / min; and a second temperature increase process of heating to a temperature exceeding 680°C at a temperature increase rate of 0.1°C / min to 3.5°C / min. The maximum reachable temperature of the calcination process can be set to 700°C to 850°C, and can also be maintained at this temperature for 1 hour to 10 hours.
[0055] Next, the calcined product (lithium-containing transition metal composite oxide) is washed with water and dehydrated to obtain a cake-like composition. The residual alkali component is removed by this washing step. The washing and dehydration can be carried out using existing known methods. Next, the cake-like composition is dried to obtain a powdery composition. The drying step can be carried out under a vacuum atmosphere. An example of drying conditions is 0.5 hours to 15 hours at a temperature of 150°C to 400°C.
[0056] The sulfonic acid compound is added to the cake-like composition obtained in the washing step, for example, or to the powder-like composition obtained in the drying step. At this time, a sulfonic acid solution may be added instead of the sulfonic acid compound or together with the sulfonic acid compound. Thus, a positive electrode active material having a sulfonic acid compound attached to the surface of particles of the lithium-containing transition metal composite oxide can be obtained. The sulfonic acid compound may be added as an aqueous dispersion. In addition, the sulfonic acid solution is preferably an aqueous solution of sulfonic acid. The concentration of sulfonic acid in the sulfonic acid solution is, for example, 0.5% by mass to 40% by mass.
[0057] Note that, since a certain amount of lithium compound remains in the cake-like composition, by adding the sulfonic acid solution to the cake-like composition, Li dissolved in water in the cake reacts with the sulfonic acid to obtain lithium sulfonate.
[0058] [negative electrode]
[0059] The negative electrode 12 has a negative electrode core 40 and a negative electrode mixture layer 41 formed on the surface of the negative electrode core 40. The negative electrode mixture layer 41 is preferably provided on both sides of the negative electrode core 40. In addition, the thickness of the negative electrode core 40 is preferably 5μm to 12μm, and more preferably 7μm to 10μm. In this case, the effect of improving the winding property of the electrode plate when making the electrode body is improved. The thickness of the negative electrode mixture layer 41 is preferably 50μm to 150μm on one side of the negative electrode core 40, for example. The negative electrode 12 is made, for example, by applying a negative electrode mixture slurry containing a negative electrode active material and a binder on the surface of the negative electrode core 40, drying the coating, and then compressing it to form the negative electrode mixture layer 41 on both sides of the negative electrode core 40, thereby being made.
[0060] The negative electrode core 40 may be made of a foil of a metal that is stable within the potential range of the negative electrode, a thin film that arranges the metal on the surface, etc., and is preferably made of copper or a copper alloy. The negative electrode core 40 made of copper or a copper alloy is stable within the potential range of the negative electrode 12. In addition, when copper or a copper alloy is used, it is easy to control the 1% compressive strength of the negative electrode core 40 within the target range. The copper alloy contains copper as the main component, and the content of copper is preferably 90 mol% or more relative to the total molar number of elements constituting the alloy.
[0061] The 1% compressive strength of the negative electrode core 40 is 300 MPa or less. By setting the 1% compressive strength of the negative electrode core 40 to 300 MPa or less, the winding property of the electrode body 14 is improved, and the increase in the diameter of the winding core associated with the decrease in the elongation at break of the positive electrode 11 can be suppressed. In other words, if the 1% compressive strength of the negative electrode core 40 exceeds 300 MPa, the winding property of the electrode plate during the manufacture of the electrode body is significantly reduced, and the diameter of the winding core will increase. In addition, from the viewpoint of further improving the winding property, the 1% compressive strength of the negative electrode core 40 is more preferably 250 MPa or less.
[0062] From the perspective of high capacity, the 1% compressive strength of the negative electrode core 40 can be 300 MPa or less, but if the 1% compressive strength of the negative electrode core 40 is too low, there is a possibility that the process stability in battery assembly will deteriorate. Therefore, the 1% compressive strength of the negative electrode core 40 is preferably 100 MPa or more, and more preferably 150 MPa or more. Therefore, the suitable range of the 1% compressive strength of the negative electrode core 40 is 100 to 300 MPa, and more preferably 150 to 250 MPa. If the 1% compressive strength of the negative electrode core 40 is within this range, a high-capacity non-aqueous electrolyte secondary battery 10 can be achieved.
[0063] The 1% compressive strength of the negative electrode core 40 is a compressive strength (1%) measured by the metal material tensile test method of JIS Z 2241. Figure 2 Schematic diagram showing the relationship between strain and stress when a tensile test is performed on the negative electrode core 40. The 1% compressive strength is the value of the stress when the strain is 1%. The 1% compressive strength of the negative electrode core 40 can be adjusted, for example, by the thickness of the negative electrode core 40 and the crystal grain size of the material of the negative electrode core 40. If the crystal grain size of the material of the negative electrode core 40 is reduced, the 1% compressive strength of the negative electrode core 40 becomes larger.
[0064] From the viewpoint of winding performance, the elongation at break of the negative electrode core 40 is preferably 10% or more, and more preferably 12% or more. In addition, if the elongation at break of the negative electrode core 40 becomes too large, there is a possibility that the process stability in battery assembly will deteriorate, so it is preferably 20% or less, and more preferably 18% or less. Therefore, an example of a suitable elongation at break of the negative electrode core is 10 to 20%, and more preferably 12 to 18%.
[0065] Among the binders contained in the negative electrode mixture layer 41, fluororesins, PAN, polyimide, acrylic resins, polyolefins, etc. can be used as in the case of the positive electrode 11, but styrene-butadiene rubber (SBR) is preferably used. In addition, the negative electrode mixture layer 41 preferably contains CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, it is suitable to use SBR in combination with CMC or its salt, PAA or its salt. The content of the binder is, for example, 0.1 to 5% by mass relative to the mass of the negative electrode mixture layer 41. It should be noted that the negative electrode mixture layer 41 may contain a conductive agent such as CNT.
[0066] The negative electrode mixture layer 41 preferably includes a carbon material and a silicon-containing material as negative electrode active materials. By using a carbon material and a silicon-containing material in combination, it is easy to take into account both high capacity and excellent cycle characteristics. The negative electrode composite material layer 41, for example, substantially only includes a carbon material and a silicon-containing material as negative electrode active materials. The content of the carbon material is preferably higher than the content of the silicon-containing material.
[0067] From the viewpoint of improving the cycle characteristics, the content of the silicon-containing material is preferably less than 20% by mass of the total mass of the negative electrode active material, and more preferably less than 15% by mass. It should be noted that in a non-aqueous electrolyte secondary battery to which a sulfonic acid compound is added to the positive electrode 11, there is a tendency for the cycle characteristics to decrease in the absence of any silicon-containing material. In addition, from the viewpoint of high capacity, the content of the silicon-containing material is preferably more than 5% by mass. Therefore, an example of a suitable range of the content of the silicon-containing material is 5 to 20% by mass of the total mass of the negative electrode active material, and more preferably 5 to 15% by mass.
[0068] The carbon material that functions as the negative electrode active material is, for example, at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon and hard carbon. Among them, artificial graphite such as blocky artificial graphite (MAG), graphitized mesophase carbon microbeads (MCMB), natural graphite such as flaky graphite, blocky graphite, and earthy graphite, or a mixture thereof are preferably used. The volume-based D50 of the carbon material is, for example, 1 μm to 30 μm, preferably 5 μm to 25 μm.
[0069] Soft carbon and hard carbon are classified as amorphous carbon with an underdeveloped graphite crystal structure. More specifically, it refers to a carbon component with a d(002) interplanar spacing of 0.342 nm or more based on X-ray diffraction. Soft carbon is also called graphitizable carbon, which is carbon that is easily graphitized by high temperature treatment compared to hard carbon. Hard carbon is also called difficult to graphitize carbon. It should be noted that in the composition of the present invention, there is no need to clearly distinguish between soft carbon and hard carbon. As a negative electrode active material, graphite and at least one amorphous carbon of soft carbon and hard carbon can be used in combination.
[0070] The silicon-containing material is a material containing Si, and as an example, silicon alloys, silicon compounds, and composite materials containing Si can be cited. Among them, composite materials containing Si are preferred. The D50 of the composite material is usually smaller than the D50 of graphite. The volume-based D50 of the composite material is, for example, 1 μm to 15 μm. It should be noted that the silicon-containing material can be used alone or in combination of two or more.
[0071] Suitable silicon-containing materials (composite materials) are composite particles comprising an ion-conducting phase, a Si phase dispersed in the ion-conducting phase, and a conductive layer covering the surface of the ion-conducting phase. The ion-conducting phase is, for example, at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase. The ion-conducting phase is a continuous phase consisting of a collection of particles finer than the Si phase. The silicide phase is a phase of a compound consisting of Si and an element more electrically positive than Si, and as an example, NiSi, Mg2Si, TiSi2, etc. can be cited. The Si phase is formed by dispersing Si in fine particles. The conductive layer is composed of a material with higher conductivity than the ion-conducting phase, and forms a good conductive path in the negative electrode mixture layer 41.
[0072] An example of a suitable composite material containing Si is a composite material having a sea-island structure in which Si is dispersed in an amorphous silicon oxide phase in a substantially uniform particle form, and having a general formula of SiO x Composite particles represented by (0<x≤2). The main component of silicon oxide may be silicon dioxide. The content ratio (x) of oxygen to Si is, for example, 0.5≤x<2.0, and preferably 0.8≤x≤1.5.
[0073] Another example of a suitable composite material containing Si is a composite particle having a sea island structure in which Si is dispersed roughly uniformly in a granular form in an ion conductive phase. The ion conductive phase, for example, contains at least one selected from the group consisting of alkali metal elements and group II elements. Furthermore, the silicate phase may contain other elements M other than alkali metal elements and group II elements. Element M may be at least one selected from the group consisting of B, Al, Zr, Nb, Ta, V, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F, W and lanthanide elements.
[0074] A suitable ion-conducting phase is a lithium silicate phase containing Li. For example, a lithium silicate phase is composed of the general formula Li 2z SiO (2+z)The phase of the composite oxide represented by (0 < z < 2). Preferably, the lithium silicate phase does not contain Li4SiO4 (Z = 2). Li4SiO4 is an unstable compound, which reacts with water to show alkalinity. Therefore, it sometimes deteriorates Si and causes a decrease in charge-discharge capacity. From the viewpoints of stability, productivity, Li ion conductivity, etc., the lithium silicate phase preferably contains Li2SiO3 (Z = 1) or Li2Si2O5 (Z = 1 / 2) as the main component.
[0075] Another example of a suitable composite material containing Si is composite particles having a sea-island structure in which fine Si is dispersed substantially uniformly in a carbon phase. The carbon phase is preferably an amorphous carbon phase. The carbon phase may also contain a crystalline phase component, but preferably has a large amount of amorphous phase component. The amorphous carbon phase is composed of a carbon material having an average crystal plane spacing of the (002) plane exceeding 0.34 nm measured by, for example, X-ray diffraction method. The amorphous carbon phase is composed of, for example, particles of amorphous carbon. It should be noted that the composite material containing a carbon phase may or may not have a conductive layer different from the carbon phase.
[0076] The conductive layer formed on the surface of the particles of the composite material is, for example, a carbon coating film composed of a conductive carbon material. As the conductive carbon material, carbon blacks such as acetylene black and Ketjen black, graphite, and amorphous carbon (non-crystalline carbon) with low crystallinity can be used. Considering the ensuring of conductivity and the diffusibility of Li ions into the interior of the particles, the thickness of the conductive layer is preferably 1 nm to 200 nm or 5 nm to 100 nm. The thickness of the conductive layer can be measured by observing the cross section of the composite material using SEM or transmission electron microscope (TEM).
[0077] [Separator]
[0078] The separator 13 uses a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, non-woven fabrics, etc. Suitable materials for the separator 13 are polyolefins such as polyethylene and polypropylene, and cellulose. The separator 13 can have a single-layer structure or a multilayer structure. In addition, a resin layer with high heat resistance such as an aromatic polyamide resin can be formed on the surface of the separator 13.
[0079] A filler layer containing an inorganic filler can also be formed at the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. As the inorganic filler, for example, oxides containing metal elements such as Ti, Al, Si, Mg, and phosphoric acid compounds can be cited. The filler layer can be formed by coating a slurry containing the filler on the surface of the positive electrode 11, the negative electrode 12, or the separator 13.
[0080] Examples
[0081] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.
[0082] <Example 1>
[0083] [Preparation of positive electrode active material]
[0084] The coprecipitation method was used to obtain [Ni 0.90 Al 0.05 Mn 0.05 The composite hydroxide represented by ](OH)2 was calcined at 500°C for 8 hours to obtain a metal oxide (Ni 0.90 Al 0.05 Mn 0.05 Next, LiOH and the above metal oxides were mixed so that the molar ratio of Li to the total amount of Ni, Al and Mn was 1.03:1 to obtain a mixture. The mixture was heated under an oxygen gas flow with an oxygen concentration of 95% (per 10 cm 3 The mixture is calcined from room temperature to 650°C at a heating rate of 2.0°C / min, and then calcined from 650°C to 780°C at a heating rate of 0.5°C / min to obtain a lithium-containing composite oxide (synthesis process). Water is added to the lithium-containing composite oxide in a slurry concentration of 1500g / L, stirred for 15 minutes, and filtered to obtain a cake-like composition (cleaning process). Powdered lithium methanesulfonate is added to the cake-like composition (addition process). The amount of lithium methanesulfonate added is 0.1% by mass relative to the total mass of the lithium-containing composite oxide. After the addition process, a drying process is performed under vacuum atmosphere at 180°C for 2 hours to obtain the positive electrode active material of Example 1. It should be noted that the presence of lithium sulfonate on the surface of the positive electrode active material was confirmed by Fourier transform infrared spectroscopy (FT-IR).
[0085] [Production of positive electrode]
[0086] The positive electrode active material, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 98:1:1, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to the positive electrode core formed by aluminum foil, the coating is dried, and after compression, the positive electrode core is cut into a specified electrode size to obtain a positive electrode having a positive electrode mixture layer formed on both sides of the positive electrode core. It should be noted that an exposed portion exposed on the surface of the positive electrode core is provided on a part of the positive electrode.
[0087] [Production of negative electrode]
[0088] Artificial graphite and SiO x(0<x≤2) are mixed in a mass ratio of 94:6 and used as a negative electrode active material. The negative electrode active material, carboxymethyl cellulose (CMC) and a dispersant of styrene butadiene rubber (SBR) are mixed in a solid component mass ratio of 98:1:1, and water is used as a dispersion medium to prepare a negative electrode mixture slurry. The negative electrode mixture slurry is applied to both sides of a negative electrode core formed by a copper foil with a thickness of 8μm. After the coating film is dried, the coating film is rolled using a roller and cut into a specified electrode size to obtain a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode core. It should be noted that an exposed portion where the surface of the negative electrode core is exposed is provided on a part of the negative electrode.
[0089] [Preparation of non-aqueous electrolyte]
[0090] LiPF6 was dissolved at a concentration of 1.2 mol / L in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (MEC) and dimethyl carbonate (DMC) in a volume ratio of 3:3:4 (25°C) to prepare a non-aqueous electrolyte.
[0091] [Selection of winding core diameter of test battery cell (wound type non-aqueous electrolyte secondary battery)]
[0092] In this specification, the diameter of the winding core of the test battery cell that can be wound is obtained according to the following method.
[0093] (1) A plurality of aluminum leads were installed on the exposed portion of the positive electrode and a nickel lead was installed on the exposed portion of the negative electrode. The positive electrode and the negative electrode were then wound into spirals with a polyolefin separator interposed therebetween using a winding core with a diameter varying from 2.8 mm to 4.5 mm in increments of 0.1 mm.
[0094] (2) The wound electrode body was visually checked for any abnormalities such as breakage or bending, and the smallest winding core diameter among the winding cores without abnormalities was defined as the winding core diameter that can be wound.
[0095] [Production of test battery cells]
[0096] An aluminum lead is installed on the exposed portion of the positive electrode, and a nickel lead is installed on the exposed portion of the negative electrode. Then, the positive electrode and the negative electrode are wound into a spiral shape using a winding core through a polyolefin separator, thereby making a wound electrode body. The winding core diameter used is the winding core diameter obtained by the above selection, and its diameter is 3.3 mm. The electrode body is housed in an outer can composed of an aluminum laminate sheet, and after the above non-aqueous electrolyte is injected, the opening of the outer can is sealed to obtain a test battery cell.
[0097] [Evaluation of initial discharge capacity]
[0098] The test cell was charged to 4.2 V at a constant current of 0.2 It at an ambient temperature of 25° C., and then charged to 0.02 It at a constant voltage of 4.2 V. Then, the discharge capacity was evaluated by constant current discharge to 2.5 V at 0.2 It.
[0099] [Evaluation of 1% compressive strength and elongation at break of negative electrode core]
[0100] After the discharge capacity evaluation, the test battery cell was disassembled and the negative electrode was taken out. According to the metal material tensile test method of JIS Z 2241, the 1% compressive strength (offset method) and elongation at break were measured for the negative electrode core punched into a dumbbell shape using Auto Graph (AG-IS) manufactured by Shimadzu. In addition, the elongation at break based on the length of the side in the width direction of the negative electrode before loading into the test battery cell was calculated. The 1% compressive strength of the negative electrode core of Example 1 was 200 MPa, and the elongation at break was 15%.
[0101] <Example 2>
[0102] In the step of adding the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 1 except that the amount of lithium methanesulfonate added was 0.3 mass % based on the total mass of the lithium-containing composite oxide.
[0103] <Example 3>
[0104] In the step of adding the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 1 except that the amount of lithium methanesulfonate added was 0.5 mass % based on the total mass of the lithium-containing composite oxide.
[0105] <Example 4>
[0106] In the positive electrode active material adding step, a test cell was prepared and evaluated in the same manner as in Example 1 except that the amount of lithium methanesulfonate added was 1.0 mass % based on the total mass of the lithium-containing composite oxide.
[0107] <Example 5>
[0108] In the process of adding the positive electrode active material, the amount of lithium methanesulfonate added was set to 0.5% by mass relative to the total mass of the lithium-containing composite oxide. In the preparation of the negative electrode, the thickness of the negative electrode core was set to 5 μm, and the winding core used in the preparation of the electrode body was changed. A test battery cell was prepared and evaluated in the same manner as in Example 1. The diameter of the winding core that can be used based on the above selection is 3.6 mm.
[0109] <Example 6>
[0110] In the process of adding the positive electrode active material, the amount of lithium methanesulfonate added was set to 0.5% by mass relative to the total mass of the lithium-containing composite oxide. In the preparation of the negative electrode, the thickness of the negative electrode core was set to 12 μm, and the winding core used in the preparation of the electrode body was changed. A test battery cell was prepared and evaluated in the same manner as in Example 1. The diameter of the winding core that can be used based on the above selection is 3.1 mm.
[0111] <Example 7>
[0112] In the process of adding the positive electrode active material, the amount of lithium methanesulfonate added was set to 0.5% by mass relative to the total mass of the lithium-containing composite oxide. In the production of the negative electrode, the strength of the negative electrode core was changed, and the winding core used in the production of the electrode body was changed. A test battery cell was produced and evaluated in the same manner as in Example 1. The diameter of the winding core that can be used based on the above selection is 3.7 mm.
[0113] <Example 8>
[0114] In the positive electrode active material adding step, a test cell was prepared and evaluated in the same manner as in Example 1 except that sodium methanesulfonate was added as a sulfonic acid compound in an amount of 0.5 mass % relative to the total mass of the lithium-containing composite oxide.
[0115] <Example 9>
[0116] In the positive electrode active material adding step, a test cell was prepared and evaluated in the same manner as in Example 1 except that lithium ethanesulfonate was added as a sulfonic acid compound in an amount of 0.5 mass % relative to the total mass of the lithium-containing composite oxide.
[0117] <Example 10>
[0118] In the step of adding the positive electrode active material, the amount of lithium methanesulfonate added was set to 0.5% by mass relative to the total mass of the lithium-containing composite oxide. In the preparation of the negative electrode, artificial graphite and SiO x A test battery cell was produced in the same manner as in Example 1 except that (0<x≤2) was mixed in a mass ratio of 85:15, and evaluation was performed.
[0119] <Comparative Example 1>
[0120] A test cell was produced and evaluated in the same manner as in Example 1 except that no sulfonic acid compound was added in the positive electrode active material addition step and the winding core used in producing the electrode body was changed. The diameter of the winding core that can be used based on the above selection was 3.0 mm.
[0121] <Comparative Example 2>
[0122] In the step of adding the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 1 except that lithium succinate was added in an amount of 0.5% by mass based on the total mass of the lithium-containing composite oxide.
[0123] <Comparative Example 3>
[0124] In the step of adding the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 1 except that lithium oxalate was added in an amount of 0.5 mass % relative to the total mass of the lithium-containing composite oxide.
[0125] <Comparative Example 4>
[0126] A test cell was prepared and evaluated in the same manner as in Example 1 except that no sulfonic acid compound was added in the step of adding the positive electrode active material, the strength of the negative electrode core was changed in the preparation of the negative electrode, and the winding core used in the preparation of the electrode body was changed. The diameter of the winding core that can be used based on the above selection is 4.0 mm.
[0127] <Comparative Example 5>
[0128] In the process of adding the positive electrode active material, the amount of lithium methanesulfonate added was set to 0.5% by mass relative to the total mass of the lithium-containing composite oxide. In the production of the negative electrode, the strength of the negative electrode core was changed, and the winding core used in the production of the electrode body was changed. A test battery cell was produced and evaluated in the same manner as in Example 1. The diameter of the winding core that can be used based on the above selection is 4.3 mm.
[0129] <Comparative Example 6>
[0130] In the process of adding the positive electrode active material, no sulfonic acid compound is added. In the production of the negative electrode, artificial graphite and SiO x (0<x≤2) were mixed at a mass ratio of 85:15 and the winding core used in producing the electrode assembly was changed. A test cell was produced and evaluated in the same manner as in Example 1. The diameter of the winding core that can be used based on the above selection was 3.0 mm.
[0131] <Comparative Example 7>
[0132] In the step of adding the positive electrode active material, the amount of lithium methanesulfonate added was set to 0.5% by mass relative to the total mass of the lithium-containing composite oxide. In the preparation of the negative electrode, artificial graphite and SiO x A test cell was prepared and evaluated in the same manner as in Example 1 except that the strength of the negative electrode core body was changed and the winding core used in the electrode body was changed (0<x≤2) at a mass ratio of 85:15. The diameter of the winding core that can be used based on the above selection is 4.3 mm.
[0133] The initial discharge capacities of the embodiments and comparative examples are shown in Tables 1 and 2, respectively. In addition, the properties of the negative electrode core (thickness, 1% compressive strength, elongation at break) and the diameter of the winding core that can be wound are shown in Tables 1 and 2. It should be noted that the initial discharge capacity in Table 1 is a relative value when the initial discharge capacity of the test battery cell of Comparative Example 1 is set to 100, and the initial discharge capacity in Table 2 is a relative value when the initial discharge capacity of the test battery cell of Comparative Example 6 is set to 100. A larger value indicates a better initial discharge capacity.
[0134] [Table 1]
[0135]
[0136] [Table 2]
[0137]
[0138] As shown in Table 1, the test cells of Examples 1 to 9, in which the positive electrode used a sulfonic acid compound and the negative electrode used a negative electrode core having a 1% compressive strength of 300 MPa or less, had improved initial discharge capacity compared to the test cells of Comparative Examples 1 to 5. In addition, the test cell of Comparative Example 1, in which the positive electrode did not use a sulfonic acid compound and the negative electrode used a negative electrode core having a 1% compressive strength of 200 MPa, had poor initial discharge capacity compared to the test cells of Examples 1 to 4. In addition, the test cells of Comparative Examples 5 and 7, in which the positive electrode used a sulfonic acid compound and the negative electrode used a negative electrode core having a 1% compressive strength of 350 MPa, had poor initial discharge capacity compared to the test cells of Examples 3 and 10.
[0139] As shown in Table 2, even when the negative electrode used a negative electrode active material having a silicon content of 15 mass %, the initial discharge capacity was improved by using a sulfonic acid compound for the positive electrode and using a negative electrode core having a 1% compressive strength of 300 MPa or less for the negative electrode.
[0140] Based on the above results, when the negative electrode uses a negative electrode core with a 1% compressive strength of less than 300 MPa, the initial discharge capacity is greatly improved by using a sulfonic acid compound in the positive electrode. On the other hand, when the negative electrode uses a negative electrode core with a 1% compressive strength greater than 300 MPa, it is difficult to improve the initial discharge capacity even if a sulfonic acid compound is used in the positive electrode.
[0141] The present disclosure is further described through the following embodiments.
[0142] Configuration 1: A non-aqueous electrolyte secondary battery, which is a wound non-aqueous electrolyte secondary battery with a positive electrode, a negative electrode and a non-aqueous electrolyte, the positive electrode comprising a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of particles of the composite oxide, the sulfonic acid compound being a compound represented by the above formula (I), the negative electrode comprising a negative electrode core and a negative electrode mixture layer formed on the surface of the negative electrode core, and the 1% compressive strength of the negative electrode core being less than 300 MPa.
[0143] Configuration 2: The nonaqueous electrolyte secondary battery according to Configuration 1, wherein the sulfonic acid compound is present in an amount of 0.1 mass % or more and 1.0 mass % or less relative to the mass of the lithium-containing transition metal composite oxide.
[0144] Configuration 3: The nonaqueous electrolyte secondary battery according to Configuration 1 or 2, wherein A in formula (I) is Li or Na.
[0145] Configuration 4: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein R in formula (I) is an alkyl group having 3 or less carbon atoms.
[0146] Configuration 5: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 4, wherein the lithium-containing transition metal composite oxide has a layered rock salt structure.
[0147] Configuration 6: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 5, wherein the negative electrode core has a breaking elongation of 10% to 20%.
[0148] Configuration 7: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 5, wherein the negative electrode core is made of copper, and a thickness of the negative electrode core is 5 μm or more and 12 μm or less.
[0149] Configuration 8: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 5, wherein the negative electrode mixture layer contains a carbon material and a silicon-containing material as negative electrode active materials.
[0150] Configuration 9: The nonaqueous electrolyte secondary battery according to Configuration 8, wherein the carbon material is at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon.
[0151] Configuration 10: The nonaqueous electrolyte secondary battery according to Configuration 8 or 9, wherein the content of the silicon-containing material is 5 mass % or more and 20 mass % or less of the total mass of the negative electrode active material.
[0152] Configuration 11: The nonaqueous electrolyte secondary battery according to any one of Configurations 8 to 10, wherein the silicon-containing material includes an ion conductive phase, a Si phase dispersed in the ion conductive phase, and a conductive layer covering a surface of the ion conductive phase.
[0153] Configuration 12: The nonaqueous electrolyte secondary battery according to Configuration 11, wherein the ion conductive phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase.
[0154] Configuration 13: The nonaqueous electrolyte secondary battery according to Configuration 11 or 12, wherein the ion conductive phase contains at least one selected from the group consisting of alkali metal elements and Group II elements.
[0155] Configuration 14: A non-aqueous electrolyte secondary battery according to Configuration 13, wherein the ion conductive phase further comprises an element M, and the element M is at least one selected from the group consisting of B, Al, Zr, Nb, Ta, V, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.
[0156] Description of Reference Numerals
[0157] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket, 30 positive electrode core body, 31 positive electrode mixture layer, 40 negative electrode core body, 41 negative electrode mixture layer.
Claims
1. A non-aqueous electrolyte secondary battery, which is a wound type non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The positive electrode comprises a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of the composite oxide particles. The sulfonic acid compound is a compound represented by formula (I), A is a Group 1 or Group 2 element, R is a hydrocarbon group, n is 1 or 2, The negative electrode comprises a negative electrode core and a negative electrode mixture layer formed on a surface of the negative electrode core. The 1% compressive strength of the negative electrode core is less than 300 MPa.
2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The sulfonic acid compound is present in an amount of 0.1 mass % or more and 1.0 mass % or less relative to the mass of the lithium-containing transition metal composite oxide.
3. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: A in formula (I) is Li or Na.
4. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: R in the formula (I) is an alkyl group having 3 or less carbon atoms.
5. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The lithium-containing transition metal composite oxide has a layered rock salt structure.
6. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The breaking elongation of the negative electrode core is greater than or equal to 10% and less than or equal to 20%.
7. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The negative electrode core is made of copper, and has a thickness of 5 μm or more and 12 μm or less.
8. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The negative electrode mixture layer contains a carbon material and a silicon-containing material as negative electrode active materials.
9. The nonaqueous electrolyte secondary battery according to claim 8, wherein The carbon material is at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon.
10. The nonaqueous electrolyte secondary battery according to claim 8, wherein The content of the silicon-containing material is 5 mass % or more and 20 mass % or less of the total mass of the negative electrode active material.
11. The nonaqueous electrolyte secondary battery according to claim 8, wherein The silicon-containing material includes an ion-conducting phase, a Si phase dispersed in the ion-conducting phase, and a conductive layer covering a surface of the ion-conducting phase.
12. The nonaqueous electrolyte secondary battery according to claim 11, wherein The ion-conducting phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase.
13. The nonaqueous electrolyte secondary battery according to claim 11, wherein The ion conductive phase includes at least one selected from the group consisting of alkali metal elements and Group II elements.
14. The nonaqueous electrolyte secondary battery according to claim 13, wherein The ion conductive phase further contains an element M, and the element M is at least one selected from the group consisting of B, Al, Zr, Nb, Ta, V, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.
Citation Information
Patent Citations
Lithium titanate powder for power storage device electrode, active substance material, and power storage device using the active substance material
JP2018006164A